Evidence of the role of nursing in the care of women who are victims of acute myocardial infarction and cardiorespiratory arrest (Research, Society and Development, 2026)
Introduction and objective: Acute myocardial infarction and subsequent cardiorespiratory arrest are becoming increasingly common in cardiovascular diseases, particularly affecting women. Nursing, responsible for care, must pay closer attention to sociocultural issues, such as gender, in addition to biological considerations, in order to understand comorbidity. Thus, the objective was to review the literature on the role of nursing in the care of women who have suffered acute myocardial infarction and cardiorespiratory arrest.Method: This is an integrative literature review. To conduct the study, the databases linked to the Virtual Health Library and PubMed were used as research sources, in order to find publications of scientific articles in the period from 2013 to 2023 (last 10 years), using the DeCS: "Nursing team" AND "Emergency" AND "Acute Myocardial Infarction" AND "Cardiopulmonary Arrest" AND "Women". Eligibility criteria were applied to filter publications that supported this study, which were submitted to semantic content analysis. Results: A synoptic table was prepared with the basic information of the articles and, with the subsequent analysis, two categories emerged: perspectives and challenges of nursing in the face of cardiac emergency services in AMI/CPR; the nurse's knowledge in the face of cardiac emergency situations. Conclusion: It is concluded that the nurse understands their role within the multidisciplinary team and their performance is indispensable in the recovery and maintenance of patients' health.